Implementing of Academic Text in Advanced Grammar Learning - Rifari Baron (VELES Voices of English Language Education Society, 2020)
Grammar has the main role in English language learning. It can be given the impact on English language skill mastery. The purposes of this study were to find deeply comprehending on grammar mastery using academic text. The method of study used one-group experimental design. Process of collecting data used observation and test. The data analysis used t-test paired two samples for means. The result of finding show that academic text gave more information deeply to identify English structure. Students have a significant increase in scores from the pre-test and post-test results. The results of this study also have implications for improving students' reading skills, especially at the level of reading comprehension and vocabulary mastery.